PENGARUH BEBERAPA JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L.) - Yohanes Sendi Leten; I Putu Sujana; I Dewa Nyoman Raka; Luh Putu Yuni Widyastuti (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
This study entitled the effect of the effect of several types of organic fertilizer on the growth and yield of mustard greens (Brassica juncea L.). The purpose of this study was to determine the effect of various types of manure on the growth and yield of mustard greens and to find out which manure gave the best growth and yield of mustard greens. This study used a randomized block design (RAK) method using various kinds of organic fertilizers, with 6 levels P0 (without fertilizer), P1 (cow manure 50 g / 10 kg soil), P2 (goat manure 50 g / 10 kg soil), P3 (chicken manure 50 g / 10 kg soil), P4 (50 g / 10 kg of soil vermicompost) and P5 (50 g / 10 kg of soil mixed fertilizer, namely 12.5 g of cow manure + 12.5 g of goat manure + 12.5 g of chicken manure + 12 vermicompost). ,5 g). The authors collected data from the parameters of plant height (cm), number of leaves (strands) leaf area (cm), total plant fresh weight (g), and total plant dry weight (g). Data is taken from each parameter. The treatment of giving type of organic fertilizer has a very significant effect on the growth and yield of mustard greens (Brassica juncea L.). The mixed organic fertilizer treatment gave the best growth and yield of green mustard (Brassica juncea L.) at a total fresh weight of 38.79 g and a total plant dry weight of 7.53 g